2022
DOI: 10.3390/ijms23084358
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP-6: At the Crossroads of Immunity, Tissue Repair and Fibrosis

Abstract: Insulin-like growth factors binding protein-6 (IGFBP-6) is involved in a relevant number of cellular activities and represents an important factor in the immune response, particularly in human dendritic cells (DCs). Over the past several years, significant insights into the IGF-independent effects of IGFBP-6 were discovered, such as the induction of chemotaxis, capacity to increase oxidative burst and neutrophils degranulation, ability to induce metabolic changes in DCs, and, more recently, the regulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 83 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…Similarly, IGFBP6 is associated with inflammation. Although the complete role of IGFBP6 is still largely unknown, it has recently been connected to cardiac remodeling and considered a biomarker for atherosclerotic plaques 22,23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, IGFBP6 is associated with inflammation. Although the complete role of IGFBP6 is still largely unknown, it has recently been connected to cardiac remodeling and considered a biomarker for atherosclerotic plaques 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…Although the complete role of IGFBP6 is still largely unknown, it has recently been connected to cardiac remodeling and considered a biomarker for atherosclerotic plaques. 22,23 Our assay included markers of systemic inflammation and vascular function. The proteins involved in systemic inflammation, SAA and CRP, showed moderately increased levels in CAD versus nCAD patients.…”
Section: Protein Combinations Stratify Risk Of Cad Patientsmentioning
confidence: 99%
“…DUOXA1 is implicated in the maturation/activation of DUOX1 that is, in turn, a NADPH oxidase known to catalyze ROS production and implicated in innate immune defense and antimicrobial function [ 47 ]. IGFBP6 is involved in the immune response, with both pro- and anti-inflammatory roles [ 48 ], and its expression has been reported to be enhanced following an increase in the fiber/starch ratio in cattle diet [ 49 ]. SLURP1 is a nicotinergic peptide known to exert an anti-inflammatory effect in the human intestinal epithelial cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP6 is involved in the immune response, with both pro- and anti-inflammatory roles [ 48 ], and its expression has been reported to be enhanced following an increase in the fiber/starch ratio in cattle diet [ 49 ]. SLURP1 is a nicotinergic peptide known to exert an anti-inflammatory effect in the human intestinal epithelial cells [ 48 ]. Notably, up-regulation of DUOXA1, DUOX1, IGFBP6 , and SLURP1 has been highlighted also with NOISeq analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies have demonstrated the downregulation of IGFBP6 expression in cancer; in contrast, several studies have shown upregulation of IGFBP6 in pancreatic cancer [ 47 ] and adrenocortical cancer [ 48 ]. Recently, it has been reported that IGFBP6 may exert immunological functions [ 49 , 50 ]. IGFBP6 was found to be highly expressed in eosinophils [ 51 ], and it has also been reported that IGFBP6 is associated with allergic asthma [ 52 ] and thymic atrophy [ 53 ].…”
Section: Discussionmentioning
confidence: 99%